Pattern of endodontic instrument separation and factors affecting its retrieval: a 10-year retrospective observational study in a postgraduate institute - Velmurugan Natanasabapathy; Aswathi Varghese; Paul Kevin Abishek Karthikeyan; Srinivasan Narasimhan (Restorative Dentistry & Endodontics, 2025)
Objectives This study aimed to assess the pattern of endodontic instrument separation, their retrievability, and factors affecting its retrieval, in a postgraduate institute. Methods Cases referred for the management of separated endodontic instruments (SEI) from 2013 to 2023 were considered for this study. Data related to demographics, tooth type, file type, and retrieval were documented in an Excel sheet. Eight prognostic factors assumed to influence the retrieval were analyzed in this study. The secondary aim was to compare the pattern of SEI and retrievability between conventional nickel-titanium files and newer generation heat-treated nickel-titanium files. Retrieval was attempted by a senior endodontist under the dental operating microscope. Various ultrasonic tips and a Broken Tool Removal loop system were used during retrieval. Simple descriptive statistics were performed. Binomial logistic regression was done to identify the effect of the eight prognostic factors on the retrieval outcome. Results A total of 190 SEI was reported. SEI occurred more often in posterior teeth than anterior teeth, mandibular arch than maxillary arch, and in larger files than smaller files. Separation occurred more often in the apical third compared to the other levels. Retrieval was attempted in 88 cases and successful in 70 cases (79.5%). The larger taper and apical position of the SEI negatively influenced the retrieval by 1.4 and 8.7 times, respectively. Conclusions Retrieval of SEI was successful in the majority of the cases. An increase in taper and apically placed SEI negatively impacted the retrieval. There was no difference in the pattern of separation nor retrievability between conventional nickel-titanium files and newer generation heat-treated nickel-titanium files.